Aspek Psikologis Organisasi Pendidikan Efektif - Muhammad Anggung Manumanoso Prasetyo; Sukatin, Sukatin (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2021)
The effectiveness of the implementation of the education system in schools is influenced by the institutional structure and organizational behavior factors. This research aims to theoretically examine the fulfillment of organizational psychology aspects effectively so as to form a conceptual model of continuing education organizational development. This type of qualitative research is literature type. Data were collected through primary sources in the form of organizational behavior concept books and other relevant research. The results showed five stages before realizing an effective organization, namely: (1) optimizing the role of managers; (2) conduct a strategic needs assessment; (3) implementation of educational structure management; (4) make behavior as a system of organizing process; and (5) creating, maintaining and developing cooperation as a network. Several efforts in creating an effective organization are through the implementation of the organic organization concept -providing more flexibility to innovate-.